Successful Palliation of a Malignant Cologastric Fistula with a Covered Self-Expanding Metal Stent - Mathilde Therese Winther Breitenbauch; Anders Tøttrup (Korean Society of Gastrointestinal Endoscopy, 2015)
When patients present with malignant cologastric fistulas, the tumor stage is often advanced and management is only palliative. We report the case of a 75-year-old man with a symptomatic cologastric fistula arising from an advanced tumor in the transverse colon, previously stented owing to malignant obstruction. An 8-cm-long covered self-expanding metal stent (COMVI enteral colonic stent; Taewoong Medical) was placed inside the primary stent, which sealed the fistula and completely alleviated the symptoms. Considering the successful outcome, we propose that insertion of a covered stent be considered in the palliative management of patients with malignant cologastric fistulas.